The study of dilatation evolution and elastic properties degradation in metals under deformation in gigacycle fatigue regime. (November 2016) - Plekhov, O.; Prokhorov, A.; Naimark, O.; Narykova, M.; Kadomtsev, A.; Betechtin, V.
Abstract: The work is devoted to the study of evolution of dilatation and elastic properties in metals under deformation in the gigacycle fatigue regime. The deformation process was realized in the ultrasonic testing machine Shimadzy USF-2000. Two sets of samples at different loading times were investigated based on the hydrostatic weighing method and the acoustic resonance method. The proposed techniques were verified using Armco iron samples and then were applied to study the evolution of defects in sub-microcrystalline titanium Grade 4. The obtained results showed that fatigue loading leads to accumulation of porosity in the samples and a corresponding decrease of their elastic properties. This effect was simulated using a statistical model of defect accumulation, which revealed the influence of the sample surface on the fatigue crack initiation sites.